2016
DOI: 10.1539/joh.15-0247-oa
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis accuracy of two vision screeners for visual health surveillance of workers who use video display terminals

Abstract: Objective: To compare the diagnostic accuracy of two vision screeners by a visual examination performed by an optometrist (gold standard) and to evaluate the concordance between both screeners and between each screener and the gold standard. Methods: This was a cross-sectional study that included computer workers who attended a routine yearly health examination. The study included administrative office workers (n=91) aged 50.2±7.9 years (mean±standard deviation), 69.2% of whom were women and 68.1% of whom use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Stereoscopes such as the Visiotest, Optec and Ergovision are recommended vision screeners regarded as fast with low maintenance costs; they are used in most European countries such as France and England. 58 In their study, Horberry et al 59 found the Titmus 2, Keystone VS-II and Optec 2500 results for vision screening to be close to those found in the gold standard visual examinations performed by optometrists. The use of stereoscopes as a vision screening method for children of schoolgoing age is still a subject of debate.…”
Section: Stereoscopic Vision Screenersmentioning
confidence: 70%
“…Stereoscopes such as the Visiotest, Optec and Ergovision are recommended vision screeners regarded as fast with low maintenance costs; they are used in most European countries such as France and England. 58 In their study, Horberry et al 59 found the Titmus 2, Keystone VS-II and Optec 2500 results for vision screening to be close to those found in the gold standard visual examinations performed by optometrists. The use of stereoscopes as a vision screening method for children of schoolgoing age is still a subject of debate.…”
Section: Stereoscopic Vision Screenersmentioning
confidence: 70%
“…Participants completed a validated battery (Table 1) of clinical assessments appropriate for this population (18). The OPTEC 2500 visual analyzer, a sensitive and specific screening tool for visual health (19) was used to assess seven visual skills: visual acuity, peripheral field of view, color discrimination, depth perception, lateral phorias, vertical phorias, and contrast sensitivity. Visual-motor integration was measured via the Beery-Buktenica Developmental Test of Visual-Motor Integration [Beery VMI™; (20)], a valid and reliable norm referenced test of visual motor integration (20).…”
Section: Methodsmentioning
confidence: 99%
“…Monocular and binocular distance VA were measured using a vision screener called Visiotest (manufacturer Essilor). This device has been shown to have a sensitivity of 100% and a specificity of 88.1% 27 to detect vision deficiency compared with an examination of vision carried out by an optometrist. Luminosity was set to 320 cd/m 2 with optotype contrast close to 100%.…”
Section: Methodsmentioning
confidence: 99%